The Role Of Artificial Intelligence In Society: The Problem Of Balance Between Technology And Spirituality (Texas Journal of Multidisciplinary Studies, 2025)
This article examines the role of artificial intelligence in society and its impact on human life, social relations, and moral values. It discusses the emergence of new forms of interaction between humans and machines during technological progress, as well as the influence of artificial intelligence on social consciousness, ethics, and spirituality. The paper highlights the urgent need to maintain balance between technology and spirituality and suggests ways to integrate intellectual technologies with moral and cultural values for the future of humanity